CXCL12 inhibits cortical neuron apoptosis by increasing the ratio of Bcl-2/Bax after traumatic brain injury. (1st April 2014) - Mao, Weifeng; Yi, Xin; Qin, Jianbing; Tian, Meiling; Jin, Guohua
<x xml:space="preserve">Abstract</x> CXCL12 and its physiologic receptor CXCR4 are involved in controlling cell survival, proliferation and migration in adult tissues. This study aimed to investigate the effects of CXCL12 on cortical neuron apoptosis in rats after traumatic brain injury (TBI) and the potential mechanisms involved. At 3 days after TBI, in situ terminal transferase d-UTP nick-end labeling assay (TUNEL) showed that the apoptotic index (AI) deceased significantly in the CXCL12 treatment group compared with the control group (p < 0.05). Immunofluorescence double-labeled staining revealed that most of the TUNEL positive cells were NeuN positive neurons. The change trends of active caspase-3 expression were similar as those of the AI. The Bcl-2:Bax ratio was upregulated in the CXCL12 group compared with the control group. However, the effect of CXCL12 could be partially reverted by the additional use of AMD3100 (a kind of antagonist of CXCR4) (p < 0.05). Our results indicated that after TBI in rats CXCL12 combing CXCR4 receptors could inhibit the caspase-3 pathway by upregulating Bcl-2:Bax ratio, which protect neurons from apoptosis.